2006
DOI: 10.2337/db05-1566
|View full text |Cite
|
Sign up to set email alerts
|

Impaired NH2-Terminal Processing of Human Proislet Amyloid Polypeptide by the Prohormone Convertase PC2 Leads to Amyloid Formation and Cell Death

Abstract: Islet amyloid, formed by aggregation of islet amyloid polypeptide (IAPP; amylin), is a pathological characteristic of the pancreas in type 2 diabetes and may contribute to the progressive loss of ␤-cells in this disease. We tested the hypothesis that impaired processing of the IAPP precursor proIAPP contributes to amyloid formation and cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 54 publications
7
99
1
Order By: Relevance
“…Surprisingly, even with rapid islet graft failure and a ∼20% reduction in insulin-positive cells in islet transplants expressing human proIAPP and lacking PC2, we were unable to detect increases in amyloid deposition or beta cell apoptosis. These observations are in contrast with our previous in vitro findings [29]. Mature amyloid fibrils appear to be less deleterious to beta cells than prefibrillar species and improvements in glucose tolerance do not always correlate with reduced amyloid formation [10].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Surprisingly, even with rapid islet graft failure and a ∼20% reduction in insulin-positive cells in islet transplants expressing human proIAPP and lacking PC2, we were unable to detect increases in amyloid deposition or beta cell apoptosis. These observations are in contrast with our previous in vitro findings [29]. Mature amyloid fibrils appear to be less deleterious to beta cells than prefibrillar species and improvements in glucose tolerance do not always correlate with reduced amyloid formation [10].…”
Section: Discussioncontrasting
confidence: 56%
“…We have previously demonstrated that cultured human proIAPP-overexpressing islets lacking PC2 develop increased amyloid formation and cell apoptosis compared with islets with normal PC2 levels [29]. We hypothesised that impaired beta cell proIAPP processing would further promote beta cell dysfunction in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Male hIAPP +/− mice on a high-fat diet form islet amyloid and develop amyloid-associated diabetes in about 1 year [20], whereas isolated islets from hIAPP +/− mice form amyloid within days during culture with elevated glucose [7,19,36]. Mice with beta cell-specific Casp8 deletion (RIPcre + Casp8 fl/fl ) were generated from Casp8 fl/fl mice [37] using the Cre/loxP recombinase system [38] and maintained by inter-breeding RIPcre + Casp8 fl/+ mice.…”
Section: Methodsmentioning
confidence: 99%
“…Three major factors contribute to human islet amyloid polypeptide (hIAPP) aggregation in type 2 diabetes: (1) presence of an amyloidogenic sequence in the hIAPP molecule [4]; (2) elevated beta cell production and secretion of hIAPP due to increased insulin demand [16,17]; and (3) impaired prohIAPP processing and/or trafficking due to beta cell dysfunction [17][18][19]. Impaired clearance of secreted hIAPP because of disrupted blood vessels in isolated islets may also potentiate amyloid formation.…”
Section: Introductionmentioning
confidence: 99%
“…Three factors have been proposed to contribute to amyloid formation in type 2 diabetes: (1) presence of an amyloidogenic sequence in the hIAPP molecule [26]; (2) elevated hIAPP production and secretion from beta cells associated with an increased demand for insulin [27][28][29] and (3) impaired prohIAPP processing associated with beta cell dysfunction [28,30,31]. The mechanisms underlying amyloid formation in cultured and transplanted human islets are still unclear but lower clearance of hIAPP secreted from beta cells due to the disrupted vasculature and beta cell dysfunction caused by islet culture and transplantation may contribute to this process.…”
Section: Introductionmentioning
confidence: 99%